Fines Hominis?: Zur Geschichte der philosophischen Anthropologiekritik - Rölli, Marc (transcript, 2015)
For a good 50 years now, theses of »vanishing humanity«, its »dissolution«, or its »end« have been haunting philosophy. People constantly speak of the »death of the subject«. From Kant, Hegel, and Marx to Nietzsche, Heidegger, Adorno, and Foucault, a philosophical skepticism is manifesting which concerns »man«, pointing beyond him. This volume sheds light on the backgrounds and meanings of these »post-modern« postulations without succumbing to polemic prejudice. The different contributions reconstruct the historically relevant criticisms that speak out against an anthropological exaltation and absolutization of »mankind«. At the same time, the volume takes a philosophical stance against the current trend of naturalist images of humanity being revived in biological sciences and brain research.